PROTEIN RESIDUE ANALYSIS OF ARTIFACTS FROM SITES HHOV-294, HIOV-57, HIOU-55, AND HIOU-61 FOR THE SYNCRUDE AURORA MINE NORTH 2003 AND 2005 PROJECTS, ALBERTA, CANADA - Puseman, Kathryn (PaleoResearch Institute); Dexter, Jaime (PaleoResearch Institute) (the Digital Archaeological Record)
Lithic artifacts from sites HhOv-294, HiOv-57, HiOu-55, and HiOu-61 were tested for possible protein residues. These sites were identified in the development area for the Syncrude Canada Limited's Aurora Mine North 2003 and 2005 project north of Fort McMurray in northeastern Alberta, Canada. The artifacts from these sites appear to date to the Early Precontact Period, approximately 9000 to 7000 BP. Protein residue analysis was undertaken to determine if proteins were present on the artifact surfaces that would provide information concerning processing/hunting of animals with these tools.